THE EFFECT OF CORPORATE GOVERNANCE AND POLITICAL CONNECTION ON FIRM PERFORMANCE IN INDONESIAN STOCK EXCHANGE - Sukiantono Tang (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
Firm performance is the capability of a business to effectively use its resources in such a way to generate operational and financial results. The purpose of this study is to find out and obtain empirical evidence about the effect of corporate governance and political connection on firm performance. This research was conducted on companies listed on the Indonesia Stock Exchange in 2017-2021. The sample results that have been selected are 859 data. The data analysis technique used is linear regression analysis. The results of this research show that corporate governance proxy family ownership has no influence on firm performance (ROA & ROE), then corporate governance proxy market to book value has influence on firm performance (ROA), political connection has no influence on firm performance ROA, but political connection has influence on firm performance ROE.